REPRESENTASI MOTIVASI DALAM LIRIK LAGU "MOTION SICKNESS" KARYA NECK DEEP : Analisis Semiotika Roland Barthes - Alfi Najahul Wathoni (2023)
Music is a medium that can be used to express the messages to those who listen to it. This study discusses a song sung by Neck Deep entitled "Motion Sickness". "Motion Sickness" is a song that tells about motivation taken from Neck Deep's journey in making the album "The Peace And The Panic" which was forged by various problems. This study aims to find a representation of motivation in the lyrics of Neck Deep's "Motion Sickness" using Roland Barthes' semiotic approach. The method used in this study is an interpretive qualitative research method. The lyrics of the song 'Motion Sickness' are then analyzed using Roland Barthes' semiotic analysis which examines the meaning of denotation, connotation, and myth in the lyrics of the song 'Motion Sickness'. From the results of the analysis that has been done, it can be seen that every meaning of denotation, connotation, and myth in the lyrics of this song contains a motivational meaning. The overall motivational representation of the lyrics of this song is that we don't give up in the middle of the road in trying to achieve our goals, even if we are in a difficult situation. Because the path that is passed is right. Keywords : meaning, Roland Barthes, semiotic, song lyrics.